Utilization of Sky Map Application in Astronomy Learning of Celestial Coordinates to Improve Students’ Understanding of Concepts and Digital Literacy for Physics Education Students - Nurulia Fajriani; Masturi Masturi (Berkala Ilmiah Pendidikan Fisika, 2023)
Using the Sky Map application in astronomy learning of celestial coordinates is intended to analyze students' level of understanding of concepts and digital literacy. Students' understanding of concepts and digital literacy was measured through tests and questionnaires. The research was focused on students who took astronomy courses in the physics department of Semarang State University, totaling 40 students. The type of research used is quantitative research. The research design carried out was pre-experimentation with one group pretest-posttest. There are two variables used, i.e. the use of Sky Map application media as the independent variable, and the improvement of the understanding of the student concept as the dependent variable. The analysis using the Wilcoxon signed rank test showed a significant increase in students' conceptual understanding after using Sky Map application media in learning with an N-Gain of 0.21, and digital literacy in the use of Sky Map application media has attained 83.47% (excellent). Therefore, it can be concluded that the use of Sky Map application media in celestial coordinates can help students understand the concept of the material as well as increase their digital literacy skills.